The influence of thermal and hypoxia induced habitat compression on walleye (Sander vitreus) movements in a temperate lake - J. L. Brooks; E. J. I. Lédée; S. M. Larocque; S. J. Cooke; E. Brown; J. D. Midwood (Movement Ecology)
Abstract Background Globally, temperate lakes are experiencing increases in surface water temperatures, extended periods of summer stratification, and decreases of both surface and deep water dissolved oxygen (DO). The distribution of fish is influenced by a variety of factors, but water temperature and dissolved oxygen are known to be particularly constraining such that with climate change, fish will likely feel the “squeeze” from above and below. Methods This study used acoustic telemetry to explore the effects of both thermal stratification and the deoxygenation of the hypolimnion on walleye (Sander vitreus) movements in a coastal embayment in Lake Ontario. Using historical water quality monitoring data, we documented seasonal and annual fluctuations in availability of both ‘suitable’ (all temperatures, DO > 3 mg/L) and ‘optimum’ (temperatures 18–23 °C, DO > 5mg/L) abiotic habitat for walleye and determined how these changes influenced walleye movements over a three-year period. Results Hypoxia (< 3 mg/L DO) was present in Hamilton Harbour every summer that data were available (32 of the 42 years between 1976 and 2018), with a maximum of 68.4% of the harbour volume in 1990. We found that thermal stratification and a hypoxic hypolimnion greatly reduced the volume of suitable habitat during our telemetry study. The reduction of suitable habitat significantly reduced walleye movement distances, however as the summer progressed, this remaining suitable habitat warmed into their thermal optimum range which was found to increase walleye movement distances. Despite the seemingly poor conditions, tagged walleye remained in the harbour for most of the year, and were the fastest growing individuals compared to other sampled coastal subpopulations in Lake Ontario. Conclusions Although we documented a reduction in the quantity of non-hypoxic habitat available to walleye, the water temperature of the remaining habitat increased throughout the summer into the physiologically optimum range for walleye and increased in metabolic quality. Many abiotic factors influence how, where, and what habitat fish choose to use, and this study reveals the importance of considering both habitat quality (temperature and dissolved oxygen) and quantity when evaluating fish habitat use and behaviour.